2020
DOI: 10.21203/rs.2.16943/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Fair Decision-making of Children and Adolescents with High-functioning Autism Spectrum Disorder from the Perspective of Dual-process Theories

Abstract: Background: Fairness has received much attention in our society. At present, the findings regarding fair decision-making in high-functioning autism spectrum disorder (HF-ASD) are inconsistent. Previous studies have shown that the fair decision-making of typically developing children is influenced by theory of mind (ToM) and executive functioning (EF). As those with HF-ASD have defects in both domains, this study aims to explore the differences in fair decision-making between children and adolescents with HF-AS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Neurotypical receivers, however, frequently reject lower offers to punish the proposer for what they feel is an unfairly small offer. Strikingly, a series of studies found that individuals with ASD act more rationally, as they are twice as likely as neurotypical individuals to accept offers that are considered 'unfair' but economically are more beneficial [34][35][36].…”
Section: Trends In Cognitive Sciencesmentioning
confidence: 99%
“…Neurotypical receivers, however, frequently reject lower offers to punish the proposer for what they feel is an unfairly small offer. Strikingly, a series of studies found that individuals with ASD act more rationally, as they are twice as likely as neurotypical individuals to accept offers that are considered 'unfair' but economically are more beneficial [34][35][36].…”
Section: Trends In Cognitive Sciencesmentioning
confidence: 99%
“…These intrinsic frontal connections are strongly associated with social and other types of reward processing as well as decision making 27 and these functions are known to be impaired in ASD. [28][29] Three other clusters involved inferior, medial and superior frontal gyri connections with thalamus, basal ganglia, cingulate, insula, occipital cortex, post-central gyrus and cerebellum associated with social cognition, language comprehension, sensory and motor processing functions, [30][31][32] all of which are impaired in ASD. [33][34][35][36] The remaining cluster primarily involved connections between the superior temporal gyrus and inferior parietal lobule with the precuneus in the default mode network, associated with self-processing, experience of agency, autobiographic and episodic memory retrieval and visuospatial imagery.…”
Section: Discussionmentioning
confidence: 99%